Decapod crustaceans associated with macroinvertebrates in Pacific Costa Rica - Salas Moya, Carolina (2021)
Decapod crustaceans are a diverse group that exploits various types of habitats in Costa Rica, where they represent 8.1% of the marine diversity of the country. This group includes families containing species with strictly symbiotic behavior, e.g., the Palaemonidae and Pinnotheridae. Despite the high diversity of decapods and the importance of symbionts in marine ecosystems, very little research has been done regarding symbiosis in Costa Rica and the Central American region. The objective of the present study is to present a check list of the species of decapods that are associated with macroinvertebrates in Pacific Costa Rica. The research was carried out using different sources, including a literature review, the Crustaceans Collection of the Zoology Museum of the University of Costa Rica, and field surveys between 1970 and 2019 along the Pacific coast of Costa Rica, and Isla del Coco, 500 km offshore. One-hundred associations are reported, of 74 species of symbiotic decapods with six host phyla. Seventy-four associated with Cnidaria, 15 with Echinodermata, four each with Annelida and Mollusca, two with Chordata, and one with Porifera. In total, there were 14 new reports of decapods occurring on Isla del Coco and four new reports of decapods for Costa Rica: Pseudocoutierea elegans, Raytheres clavapedatus, Tuleariocaris holthuisi, and Calyptraeotheres pepeluisi. These results highlight the need to conduct more detailed studies to determine the real diversity and ecological importance of the associations between marine organisms.